The effect of testing & environmental conditions on the properties of injection moulded glass fibre reinforced polyamide 6 composites / Asfarina Amir Hassan - Asfarina, Amir Hassan (2011)
Polyamide 6 (PA6) with various loading of short glass fibres, SGF (2%, 5%, 8%, 10% & 16% Vf) were prepared by injection moulding. The mechanical properties of composites were studied through tensile and impact tests. Composites were subjected to a series of mechanical tests at various testing conditions. The aim of the investigations was to show in which way the SGF content and testing conditions influence the materials behaviour. For different conditions, SGF/PA6 composites were subjected to dry as moulded (DAM), 50% RH and wet conditions. Results showed that composites strength decreases as moisture is introduced and temperature is raised. The melting temperatures as well as thermal stability of composites were also studied by DSC and TGA techniques respectively. The composites were also subjected to DMA analysis to examine the viscoelastic behaviour of materials under periodic stress. TGA analyses revealed that the thermal stability increase with an increase in the SGF content. DSC results showed that as the glass fibre content increases, the degree of crystallinity also decrease. Mechanical test showed that the tensile modulus and tensile strength increase steadily while the elongation at break decrease with an increase in the SGF content and/or strain rate. The toughness of moulded materials was characterised using linear elastic fracture mechanics approach. The critical strain energy release rate, (Gc) increases as the glass fibre loading increases. The reduction in ductility and toughness are attributed to the constrained mobility of polymer chains in the presence of SGF.